Percutaneous Occlusion of Patent Ductus Arteriosus for an Elderly Patient With Refractory Congestive Heart Failure. (February 2018) - Shoji, Satoshi; Kanazawa, Hideaki; Yanagisawa, Ryo; Tanaka, Makoto; Fukuoka, Ryoma; Akita, Keitaro; Kimura, Mai; Arai, Takahide; Kawakami, Takashi; Hayashida, Kentaro; Yuasa, Shinsuke; Tsuruta, Hikaru; et al.
Abstract : Supplemental Digital Content is available in the text.